Design of a Semi-Automatic Hydraulic Extruder Machine for the Manufacture of Pastry Bricks Using Vdi 2221 - Nieto Yali, Cristhian Luis (2024)
Abstract—The main objective of this research work is to design a semi-automatic hydraulic extruder machine to produce pastry bricks for Bricks Imperio. The aim is to achieve a production rate of 700 bricks per hour at a maximum cost of 12,000 dollars. For this purpose, an interpretative theoretical framework of similar products is carried out, and simulation software is used to test the theoretical concepts in real-world conditions. Following the methodology recommended by the German Engineering Association VDI 2221, a detailed list of requirements is drawn up, existing technology is analyzed, and mechanical, electrical, and hydraulic functions are designed. The design is verified with CAD software, and a techno- economic analysis is carried out. As a result, the successful design of the semi-automatic hydraulic extruder machine for the manufacture of pastry bricks is achieved, with a cost of 11,992.00 dollars and a production capacity of 700 bricks per hour.